Assessing the Impact of Project-Based Learning on Sustainable Knowledge Construction - Siyam, Ul Alam; Md., Ashrafuzzaman; Md., Rabbi Khan (INTI International University, 2025)
Project-based learning (PBL) has become a transformative pedagogy in sustainable education, providing learning experiences in which students blend theoretical knowledge and experience. As educational institutions increasingly work with PBL, it needs to be assessed to ensure sustainable outcomes for teaching and learning. This study employs a convergent parallel mixed-method approach to explore participants’ perceptions and experiences of how PBL influences learners to ensure sustainable knowledge construction in higher education. It also explores critical thinking, communication, and collaboration skills, examining student engagement and motivation levels in PBL activities and identifying factors that influence PBL effectiveness in sustainable education contexts. Data were collected from students through surveys and semi-structured interviews. The quantitative results showed that students improved their collaboration, self-directed learning, communication, technical, and knowledge-integration skills. Qualitative data indicated that PBL encourages students to apply theoretical concepts to real-world problems, thereby helping them achieve lifelong learning. Research findings suggest that project-based learning significantly enhances student engagement, problem-solving abilities, and critical thinking skills.